THE MAIN CHARACTER’S MARRIAGE IN THE NOVEL PERSUASION BY JANE AUSTEN - Sindy, Nurani; Saprudin, Saprudin; Sukmawaty, Fenty (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
This study examines the social life of the character Anne in the novel Persuasion, a classic novel written by Jane Austen. There are two formulations of the problem. The first issue is about how Anne Elliot's character is described in Persuasion. The second problem is about how gender and social class issues are related to Anne's life. The method used in this research is descriptive qualitative. Anne Elliot is a wonderful person, charming, friendly, intelligent, open-minded, multi-talented and helpful. In the Middle Ages, women were considered powerless to make decisions and had to obey the rules of family and society, not preventing Anne from fighting for what she really wanted. Anne, who came from a prominent family where her father was in a high position at work, was willing and able to break the rules against relations of different social status and class. His awareness and power to make decisions eventually lead him to true love and true happiness, without interference, coercion, and persuasion from others.